2021
DOI: 10.1007/s13668-021-00373-1
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Implications of Patients with Dysautonomia and Hypermobility Syndromes

Abstract: Purpose of Review Dysautonomia and hypermobility syndrome are two distinct but often overlapping clinical conditions that are recognized for their complex multiorgan system afflictions. The purpose of this review is to investigate dietary strategies to reduce symptoms and augment quality of life in this growing patient population. Recent Findings There is increasing evidence supporting dietary modifications to include food rich in probiotics and prebiotics, along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 96 publications
(111 reference statements)
0
9
0
Order By: Relevance
“…A review of thiamine deficiency and related neurological and psychiatric disorders showed that thiamine deficiency can cause various neurological symptoms, including dysautonomia 3 . Additionally, individuals with postural orthostatic tachycardia syndrome, which is a type of dysautonomia, have been shown to have vitamin B12 and thiamine deficiency 9 . Although these studies provide some evidence regarding the relationship between thiamine deficiency and autonomic nerve failure, further studies are warranted to determine the extent of this relationship and whether other factors contribute to dysautonomia.…”
Section: Discussionmentioning
confidence: 99%
“…A review of thiamine deficiency and related neurological and psychiatric disorders showed that thiamine deficiency can cause various neurological symptoms, including dysautonomia 3 . Additionally, individuals with postural orthostatic tachycardia syndrome, which is a type of dysautonomia, have been shown to have vitamin B12 and thiamine deficiency 9 . Although these studies provide some evidence regarding the relationship between thiamine deficiency and autonomic nerve failure, further studies are warranted to determine the extent of this relationship and whether other factors contribute to dysautonomia.…”
Section: Discussionmentioning
confidence: 99%
“…19,23,24 When treating MCAD, removing gluten, lactose, preservatives, additives, artificial sweetener, and alcohol (especially red wine, beer, and champagne) may minimize reactions. 19,25,26 Additionally, those struggling with MCAD may wish to try a dietician-supervised elimination diet, which has demonstrated improvement in over 70% of cases. 27 Recommended foods to avoid typically have high histamine levels, such as leftover foods, fermented foods, and canned fish.…”
Section: Nutritionmentioning
confidence: 99%
“…Nutrition plays a key role in managing chronic illness, such that a poorly managed diet can contribute to musculoskeletal pain. Although research on SJH and nutrition is limited, nutritional intervention and dietary supplements may reduce symptoms and improve quality of life 19,20. Eating habits alter the chemical environment of the gastrointestinal tract and can affect degenerative diseases 21.…”
Section: Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water consumption maybe an important strategy for prevention and treatment of obesity (13). Adequate uid intake associate with gastrointestinal health (14), better cognitive function (15), blood glucose status (16) and reduced mortality risk (17). Some studies expressed that sugar-sweetened beverage (SSB) consumption increase the risk of blood pressure, overweight, diabetes and cardiovascular diseases (18,19) while other studies recommend SSB as bene cial factor for better metabolic status (20).…”
Section: Introductionmentioning
confidence: 99%